Telomere fragment induced amnion cell senescence: a contributor to parturition? - Polettini, Jossimara [UNESP]; Behnia, Faranak; Taylor, Brandie D.; Saade, George R.; Taylor, Robert N.; Menon, Ramkumar (Public Library Science, 2015)
Oxidative stress (OS)-induced senescence of the amniochorion has been associated with parturition at term. We investigated whether telomere fragments shed into the amniotic fluid (AF) correlated with labor status and tested if exogenous telomere fragments (T-oligos) could induce human and murine amnion cell senescence. In a cross-sectional clinical study, AF telomere fragment concentrations quantitated by a validated real-time PCR assay were higher in women in labor at term compared to those not in labor. In vitro treatment of primary human amnion epithelial cells with 40 μM T-oligos ([TTAGGG]2) that mimic telomere fragments, activated p38MAPK, produced senescence-associated (SA) β-gal staining and increased interleukin (IL)-6 and IL-8 production compared to cells treated with complementary DNA sequences (Cont-oligos, [AATCCC]2). T-oligos injected into the uteri of pregnant CD1 mice on day 14 of gestation, led to increased p38MAPK, SA-β-gal (SA β-gal) staining in murine amniotic sacs and higher AF IL-8 levels on day 18, compared to saline treated controls. In summary, term labor AF samples had higher telomere fragments than term not in labor AF. In vitro and in situ telomere fragments increased human and murine amnion p38MAPK, senescence and inflammatory cytokines. We propose that telomere fragments released from senescent fetal cells are indicative of fetal cell aging. Based on our data, these telomere fragments cause oxidative stress associated damages to the term amniotic sac and force them to release other DAMPS, which, in turn, provide a sterile immune response that may be one of the many inflammatory signals required to initiate parturition at term.